2013
DOI: 10.1016/j.jjcc.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol promotes rat aortic vascular smooth muscle cell proliferation via increase of homocysteine and oxidized-low-density lipoprotein

Abstract: Based on these results, we conclude that ethanol apparently exerts aortic VSMC proliferation through increase in homocysteine and Ox-LDL-mediated oxidative stress, which in turn trigger proatherogenic changes in the aortic wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…The optimal safe dose for human pregnancy needs to be clinically defined. The association of alcohol during embryonic exposure with elevated HCy levels and FA prevention (Han et al, ; Serrano et al, ) has been confirmed since then by multiple studies in the alcohol literature (Shirpoor et al, ; Kharbanda et al, ; Kruman and Fowler, ; Prior et al, ). It appears that folate deficiency is associated with the observed dyslipidemia in the fetus and placenta from a binge level of alcohol exposure.…”
Section: Discussionmentioning
confidence: 89%
“…The optimal safe dose for human pregnancy needs to be clinically defined. The association of alcohol during embryonic exposure with elevated HCy levels and FA prevention (Han et al, ; Serrano et al, ) has been confirmed since then by multiple studies in the alcohol literature (Shirpoor et al, ; Kharbanda et al, ; Kruman and Fowler, ; Prior et al, ). It appears that folate deficiency is associated with the observed dyslipidemia in the fetus and placenta from a binge level of alcohol exposure.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, there is often significant adventitial remodeling in response to vessel injury and adventitial myofibroblasts are believed capable of translocating to the neo-intima and differentiating to vSMC and in this way also contribute to vascular lesion formation (Scott et al 1996; Shi et al 1996). In addition to alcohol effects on lipoproteins(Wakabayashi 2015; Hao et al 2015), we and others have described potentially important effects of alcohol on vSMC growth and migration(Sayeed et al 2002) (Cullen et al 2005; Cahill and Redmond 2012; Shirpoor et al 2013), as well as on vascular endothelial cells(Morrow et al 2008) and monocytes (Cullen et al 2005; Muralidharan et al 2014). The emergence of the concept that resident vascular stem cells, in addition to de-differentiation of vSMC and myofibroblasts as mentioned above, may become activated and contribute to arterial pathology(Orlandi 2015), together with the lack of information as to whether alcohol can regulate stem cells in the adult vessel, provoked our present study.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have reported that the blood homocysteine level is significantly associated with calcified plaque and the severity of CAD, assessed by computed tomography angiography and the Gensini scoring system (5-7). While there is published evidence supporting the pathophysiologic mechanisms linking homocysteine to atherosclerosis, including an increase of oxidative stress and promotion of the oxidation of low-density lipoprotein (8), stimulation of vascular smooth muscle cell proliferation (9,10) and inducement of vascular inflammation and endothelial dysfunction (11), certain studies did not support the predictive effect of homocysteine on atherothrombotic cardiovascular diseases (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%